KONSUMSI DAN EFISIENSI PAKAN PADA IKAN KERAPU BEBEK (Cromileptes altivelis) YANG DIPUASAKAN SECARA PERIODIK - Edy Yuwono; Purnama Sukardi; Isdy Sulistyo (The East Java Biological Society, 2005)
The objective of the research was to find out the effect of repeating cycle of feed deprivation followed by fixed refeeding on the food consumption and feed efficiency of grouper Cromileptes altivelis. The experimental fish weight was 10.86 ± 1.42 gram. The treatments included: (P1) group received repeating cycles of 1 day food deprivation followed by 2 days refeeding in 14 cycles; (P2) group received repeating cycle of 1 day food deprivation followed by 3 days refeeding in 10 cycles; (P3) group received repeating cycle of 1 day food deprivation followed by alternating 2 and 3 days refeeding in 12 cycles and; (K) group fed daily as control. Each treatment was assigned to 3 aquaria containing 150 l recirculated sea water according to completely randomized design. Twenty individuals were stocked in each aquaria. The fishes were fed with floating pellet twice a day at 09.00 and 15.00 to satiation for four weeks. Water quality was monitored. The results showed that repeating cycle of food deprivation followed by fixed refeeding affected food consumption and feed efficiency in grouper Cromileptes altivelis. Food consumption of fishes from treatment groups showed lower food consumption than control, but they showed higher daily food consumption and feed efficiency. This phenomenon could be applied in practical feeding management for application to mariculture.